National Health Accounts Data from 1996 to 2010 : A Systematic Review - Bui, Anthony L.; Lavado, Rouselle F.; Johnson, Elizabeth K.; Brooks, Benjamin P. C.; Freeman, Michael K. (World Health Organization, 2015)
We downloaded country-generated NHA reports from the World Health Organization global health expenditure database and the Organisation for Economic Co-operation and Development (OECD) StatExtract website. We also obtained reports from Abt Associates, through contacts in individual countries and through an online search. We compiled data in the four main types used in these reports: (i) financing source; (ii) financing agent; (iii) health function; and (iv) health provider. We combined and adjusted data to conform with OECD’s first edition of A system of health accounts manual, (2000).